Analisis Pengaruh Kualitas Mutu Pelayanan Kesehatan Ibu dan Anak terhadap Kepuasan Ibu Hamil Di Puskesmas Topore Kabupaten Mamuju - Safitri, Norma; Burhanuddin, Yuniarti Eka; Syahrianti, Syahrianti; Ekawati, Erni Agit; Putri, Hanriska Awidiya (Yayasan Mandar Indonesia, 2025)
The quality of maternal and child health (MCH) services plays a key role in pregnant women’s satisfaction. This cross-sectional study analyzed the impact of MCH service quality on satisfaction among 60 pregnant women at Topore Health Center, Mamuju Regency, using purposive sampling. Data were collected via the SERVQUAL questionnaire covering five service quality dimensions (physical evidence, reliability, responsiveness, assurance, empathy) and satisfaction levels. Analysis with chi-square and linear regression showed an average service quality score of 3.45 (scale 1 – 5), with responsiveness highest (3.8) and physical evidence lowest (3.2). About 65% of respondents were satisfied, while 35% were dissatisfied due to long waits and inadequate facilities. Service quality was significantly associated with satisfaction (p = 0.001) and explained 58% of its variance (R² = 0.58). The study concludes that MCH service quality significantly affects pregnant women’s satisfaction at Topore Health Center.